Analisa Dampak Lingkungan Ibu Kota Nusantara - Arfiga Wahyu; Aldri Frinaldi (CV. ITTC INDONESIA, 2023)
The purpose of this research is to look at the New Capital City in the View of Environmental Law. This research uses a qualitative method and type of literature study to gain a better understanding of a topic or phenomenon by looking at literature and other relevant sources. To obtain data, researchers conduct research and analyse various references, such as books, scientific journals, articles, and other documents related to the research topic. Then, they draw conclusions from their research and findings. This research shows that the government is responsible for monitoring and supervising environmental impacts. The concept of responsibility is incorporated into environmental law, where parties involved in the project are responsible for supervising and managing environmental impacts. They must undertake remedial and compensatory measures in the event of environmental damage. This supervision is carried out to ensure that the project runs in accordance with applicable regulations and does not cause unwanted environmental impacts.